The Relationship of Healthy Living Behavior and Scabies Disease Case in Students at Raudlatul Ulum 2 - Emiliana R, Theresia; Maria, Lilla; Yekti M, Risna (Green Publisher Indonesia, 2022)
Santri who live in pesantren is a vulnerable group to scabies disease because clean and healthy living behaviors, especially individual hygiene, get less attention from students and pesantren managers. This study uses analytical correlation methods with correlational approaches at identifying the relationship of clean and healthy living behavior with the incidence of scabies disease in Santri in Raudlatul Ulum 2 Putukrejo Gondanglegi Village with a population of 150 Santri , sampling using a simple random sampling approach with Study sample of 110 students. Data collection is done using questionnaires, namely demographic data questionnaires, clean and healthy living behavior questionnaires and scabies disease questionnaires using spearman correlation tests. This study proved that most of the respondents of 66 (60%) had a healthy living behavior of bad and sufficient categories and overall 66 respondents (100%), while respondents with good categories as many as 44 respondents (40%) did not experience scabies disease. Based on the results of the rho Spearman correlation test obtained a value of p 0.000 (p<0.05) which means there is a relationship between clean and healthy living behavior with scabies disease. While the correlation coefficient value, r = -0.907 which means that the direction of the negative correlation with the correlation coefficient is very strong. This means that the worse the clean and healthy living behavior, the higher the suffering from scabies disease. Based on the results of research, that to reduce the incidence of scabies disease, one of them is to improve clean and healthy living behaviors.